ANALYSIS OF THE DILEMMA OF CREATING SUSTAINABLE PRODUCTION MANAGEMENT SYSTEMS: SUPPORT CASES - Kulinich, Tetiana (European Science, 2023)
The analysis of the dilemma of creating sustainable production management systems is an extremely important task for modern organizations. This is driven by the fact that sustainability in production management entails the ability of a manufacturing enter